Risk assessment through rice (Oryza sativa) in sludge treated soil - Verma, Anil Kumar; Singh, R D; Datta, S P; Kumar, S; Mishra, Rahul; Trivedi, Vivek K; Sharma, V K; Meena, M C (The Indian Journal of Agricultural Sciences, 2020)
An experiment was carried out on basmati rice (Oryza sativa, var. Pusa Basmati 1121) using IARI soil to assess the effect of applied sludge on different soil properties, metals content in rice grain and computed hazard quotient for suitability of rice grain for human consumption. The different doses of sludge were used as treatments 0, 10, 20, 30, 40 and 50 g/kg.The results indicated that applied sludge @ (50 g/kg) reduced the pH from 7.98 (control) to 7.21 of sludge amended soil. Whereas, the EC increased from 0.22 (control) to 1.33 dS/m under applied @ 50 g sludge/kg of soil. The organic carbon content and cation exchange capacity were found highest in 50 g sludge/ kg soil treatment as compared to control. DTPA Extractable metals in post- harvest soil were significantly higher in sludge application @ ≥ 30 g/kg treatments. The value of HQ ranged from 0.05 to 0.49 and 0.02 to 0.09 for Pb and Cd, respectively across the various treatments of sludge addition. It can be concluded that risk assessment for intake of metals through consumption of rice by human indicated that application of sludge should be restricted up to 20 g/ kg unfit for rice cultivation.